Kidney Intragraft Homing of De Novo Donor‐Specific HLA Antibodies Is an Essential Step of Antibody‐Mediated Damage but Not Per Se Predictive of Graft Loss. Issue 3 (14th September 2016) - Nocera, A.; Tagliamacco, A.; Cioni, M.; Innocente, A.; Fontana, I.; Barbano, G.; Carrea, A.; Ramondetta, M.; Sementa, A.; Basso, S.; Quartuccio, G.; Klersy, C.; et al.
Abstract : Donor‐specific HLA antibody (DSA)‐mediated graft injury is the major cause of kidney loss. Among DSA characteristics, graft homing has been suggested as an indicator of severe tissue damage. We analyzed the role of de novo DSA ( dn DSA) graft homing on kidney transplantation outcome. Graft biopsy specimens and parallel sera from 48 nonsensitized pediatric kidney recipients were analyzed. Serum samples and eluates from graft biopsy specimens were tested for the presence of dn DSAs with flow bead technology. Intragraft dn DSAs (gDSAs) were never detected in the absence of serum dn DSAs (sDSAs), whereas in the presence of sDSAs, gDSAs were demonstrated in 72% of biopsy specimens. A significantly higher homing capability was expressed by class II sDSAs endowed with high mean fluorescence intensity and C3d‐ and/or C1q‐fixing properties. In patients with available sequential biopsy specimens, we detected gDSAs before the appearance of antibody‐mediated rejection. In sDSA‐positive patients, gDSA positivity did not allow stratification for antibody‐mediated graft lesions and graft loss. However, a consistent detection of skewed unique DSA specificities was observed over time within the graft, likely responsible for the damage. Our results indicate that gDSAs could represent an instrumental tool to identify, among sDSAs, clinically relevant antibody specificities requiring monitoring and possibly guiding patient management. Abstract : This systematic evaluation of de novo donor‐specific HLA antibodies in kidney biopsies and parallel sera collected longitudinally from a pediatric kidney transplant cohort demonstrates that intragraft donor‐specific antibodies appear before development of antibody‐mediated histological lesions, and, over time, maintain a consistently skewed antibody pattern when compared to the circulating specificity profile.